A study on building facades defects and causes in goverment buildings at Putrajaya - Rosmawati binti Ismail Effendi (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2010)
The facade plays a key role as both a barrier and a filter between the comfortable 'indoors' and the uncontrolled 'outdoors'. The degree to which the facade of a building embraces maintenance considerations has a major impact on its performance. In Malaysia, new buildings are erected everyday with modern design featuring complex building facade design which has common problems often found in different types of building facades. These problems have implications in the design, constructions and maintenance of buildings. Every building facade should always be maintained to a high standard so that it will look more value in its appearance and a longer life span. The value of buildings depends on the quality of the maintenance invested in them. Maintenance management involves obtaining maximum benefit from the investment made on the maintenance activities. Maintenance in buildings in Malaysia is on the increase regardless of size, type, location, and ownership. It is necessary to rectify building facade defects and for maintenance purposes as facades is exposed to the climatic condition. The study will find out the building facade defects and other maintenance problems that are heavily attributed to design deficiencies, material limitations and lack of maintenance knowledge. To achieve this aim, three objectives have been set: to identify the types of common building facade defects, to identify its effect on maintenance and to relate the facade defects with maintenance and to recommend the appropriate solutions to improve the establishment of standard building facade maintenance in Malaysia. A study was conducted in three government buildings in Putrajaya to identify the fa9ade defects and its effect on maintenance. The data were analyzed using Relative Index formula. The current maintenance management procedures in Malaysia are, however, condition and reactive based. The weaknesses in the current procedures are the primary problems because they do not explicitly link maintenance needs with building performance with respect to the building users. Findings show that main problems that the maintenance contractors are currently facing are caused by building design deficiencies, poor construction quality, and choice of building material which affects maintenance.